Method for producing starch-based water absorptive resin composition

By introducing ionic functional groups into rice starch and crosslinking the modified starch, the method enhances the water-absorbing performance of starch-based resin compositions, addressing the insufficient water absorption of existing compositions.

JP2025038888APending Publication Date: 2025-03-19SANYO CHEM IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024152783
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-07
Filing Date
2024-09-05
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Existing starch-based water-absorbent resin compositions do not have sufficient water-absorbing performance, which is a limitation in their application for hygienic products.

Method used

A method involving a modification step to introduce ionic functional groups into rice starch using a functional group introducing agent, followed by a crosslinking step to enhance the water-absorbing properties of the starch-based resin composition.

Benefits of technology

The method results in a starch-based water-absorbing resin composition with excellent water absorption performance, making it suitable for use in hygienic products and other applications where water retention is critical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038888000001
    Figure 2025038888000001
  • Figure 2025038888000002
    Figure 2025038888000002
Patent Text Reader

Abstract

To provide a method for producing a starch-based water absorptive resin composition which is excellent in water absorption performance.SOLUTION: A method for producing a starch-based water absorptive resin composition includes: a modification step (A) of obtaining modified starch having an ionic functional group using rice and a functional group-introducing agent; and a crosslinking step (B) of crosslinking the modified starch.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing a starch-based water-absorbing resin composition. [Background technology]

[0002] Conventionally, absorbent resins made from partially neutralized salts of polyacrylic acid or polymethacrylic acid have been used as absorbent resins for use in hygiene products such as disposable diapers and sanitary napkins, which are daily necessities. However, since absorbent resins made from polyacrylic acid or the like place a heavy burden on the environment, absorbent resins made from biodegradable polysaccharides such as starch have been proposed (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2007-222704 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the water-absorbing resin composition described in Patent Document 1 has a problem in that it does not have sufficient water-absorbing performance.

[0005] An object of the present invention is to provide a method for producing a starch-based water-absorbing resin composition having excellent water-absorbing properties. [Means for solving the problem]

[0006] The present invention provides a method for producing a starch-based water-absorbent resin composition, comprising: a modification step (A) of obtaining modified starch having an ionic functional group using rice and a functional group-introducing agent; and a crosslinking step (B) of crosslinking the modified starch. [Effects of the Invention]

[0007] According to the present invention, a starch-based water-absorbing resin composition having excellent water-absorbing properties can be obtained. DETAILED DESCRIPTION OF THE INVENTION

[0008] <Method for producing starch-based water-absorbent resin composition> The method for producing a starch-based water-absorbent resin composition of this embodiment includes a modification step (A) of obtaining modified starch having ionic functional groups using rice and a functional group-introducing agent, and a crosslinking step (B) of crosslinking the modified starch. The production method of this embodiment uses rice as a raw material, which allows sufficient introduction of functional groups into rice starch derived from rice, and therefore can produce a starch-based water-absorbent resin composition with excellent water absorption performance.

[0009] [Modification step (A)] The modification step (A) is a step of obtaining modified starch having ionic functional groups using rice and a functional group-introducing agent.

[0010] [Rice] There are no limitations on the type of rice used in the modification step (A), and any known rice can be used, regardless of its cultivation method, including rice of the Asiatic rice (Asiatic species, Sativa species), Japonica species (Japanese-type rice, Japonica type), Indica species (Indica-type rice, Indica type), and Javanica species (Java-type rice, Javanica type), etc. Different varieties of rice may also be used in combination.

[0011] The rice can be used without any restrictions as long as it is obtained by removing the outer husk from harvested rice grains. The rice may be rice flour milled by a known method (roll milling, pounder milling, milling using a high-speed grinder that rotates a disk with pins at high speed, air milling, etc.).

[0012] When rice flour is used in the modification step (A), there is no particular limitation on the particle size of the rice flour, but the mass average particle size is preferably 30 μm or more and 300 μm or less. When the rice flour is used in the modification step (A), the reaction proceeds efficiently when a charge is applied, which is preferable.

[0013] The rice may be rice that has become unsuitable for consumption due to a long period of time having passed since production, or broken rice that is generated during processing.

[0014] The rice starch contained in the rice may have an α structure (amorphous structure) or a β structure (crystalline structure), but an α structure is preferred because it allows for efficient introduction of functional groups.

[0015] Methods for obtaining rice starch with an α-structure (gelatinization treatment) include soaking rice containing starch with a β-structure in water, boiling the rice after immersion in water, and other heat treatment methods such as steaming. Other methods that can be used include applying shear force while heat-treating the rice, or applying shear force after heat-treating the rice. Furthermore, gelatinization treatment can be carried out during the modification step (A) by, for example, using a basic substance when reacting the rice starch with the polar group-introducing agent in the modification step (A), or these procedures can be combined. Furthermore, rice that has returned to a β-structure after gelatinization treatment can be gelatinized again by heat treatment or other methods.

[0016] The rice may be in a moist state or in a dry state (such as dehydrated rice and / or rice flour, and dried rice and / or rice flour).

[0017] [Functional group introduction agent] Examples of the ionic functional group include cationic functional groups (amino groups, ammonium groups, etc.) and anionic functional groups (carboxyl groups, phospho groups, sulfo groups, etc.). Among these, carboxyl groups are preferred from the viewpoint of introducing a sufficient amount of ionic functional groups into rice starch.

[0018] Examples of functional group-introducing agents for introducing carboxyl groups into rice starch include halogenated alkylcarboxylic acids (salts) such as monochloroacetic acid (salts) and polybasic acids (oxalic acid, malonic acid, maleic acid, fumaric acid, succinic acid, sulfosuccinic acid, malic acid, itaconic acid, citric acid, and their anhydrides). Among these, sodium chloroacetate is preferred from the viewpoint of introducing a sufficient amount of ionic functional groups into rice starch. Note that the term "acid (salt)" refers to an acid and / or an acid salt, and examples of the acid salt include alkali metal acid salts.

[0019] Examples of functional group introducing agents for introducing phospho groups into rice starch include chloromethyl dibenzyl phosphate and chloromethyl di-t-butyl phosphate.

[0020] Examples of functional group introducing agents for introducing sulfo groups into rice starch include fuming sulfuric acid.

[0021] The number of ionic functional groups in the modified starch is preferably 0.1 to 1.5 per monosaccharide unit constituting the starch, more preferably 0.3 to 0.8. Within this range, sufficient water absorption performance can be obtained. When the ionic functional groups are carboxyl groups, the number of ionic functional groups in the modified starch can be measured by the following method. [Number of ionic functional groups (carboxyl groups) in modified starch per monosaccharide unit] Five grams of the modified starch obtained in the modification step (A) was pressed into a Briquestting Ring (made of vinyl chloride, 35 mm diameter, 5 mm thick) using a Shimadzu Briquest Press MP-35 to form pellets, and the sodium atomic concentration was determined using semi-quantitative analysis with a fully automated wavelength-dispersive X-ray fluorescence analyzer (instrument name: Axios, manufacturer: PANalytical) under X-ray excitation conditions of 20 kV voltage, 120 mA current, and vacuum chamber atmosphere, using the quantitative analysis software Uniquant. The number of ionic functional groups (DS) per monosaccharide unit constituting the starch was calculated by substituting the obtained sodium atomic concentration value for Na in the following equation: DS = (162 × Na) / (23-80 × Na)

[0022] The modification step (A) can be carried out by mixing the rice and the functional group introduction agent in the presence of a reaction solvent such as water and a lower alcohol (e.g., isopropanol), optionally in the presence of a basic compound such as sodium hydroxide, while heating as needed. The mixing temperature and mixing time can be adjusted depending on the reaction scale and the number of ionic functional groups to be introduced, but from the viewpoint of keeping the number of ionic functional groups per constituent monosaccharide residue of starch within the above-mentioned preferred range, the mixing temperature is preferably 30 to 90°C, and the mixing time is preferably 0.5 to 5 hours.

[0023] The weight ratio of the reaction solvent to the total weight of the rice can be changed depending on the device used to mix the rice and the functional group introduction agent.

[0024] As the apparatus used for mixing the rice and the functional group-introducing agent in the modification step (A), known mixing apparatuses such as a twin-screw kneader, a mixing vessel equipped with paddle-type stirring blades, a Henschel mixer, and a planetary mixer can be used.

[0025] The weight of the functional group introduction agent used in the modification step (A) is preferably 40 to 60 parts by weight per 100 parts by weight of the rice, from the viewpoint of the efficiency of introduction of the ionic functional group.

[0026] The production method of this embodiment may include a purification step of separating and purifying the modified starch obtained in the modification step (A). The purification step includes, for example, a step of filtering the reaction mixture obtained in the modification step (A) and recovering the filtration residue. The filtration of the reaction mixture can be carried out by a known method using a filter. The filtration residue recovered in the purification step can be washed and dried as necessary. Washing can be carried out by mixing the filtration residue with methanol as a washing liquid, followed by filtration, for example. Drying can be carried out by a known method using a forward-flow dryer, for example.

[0027] [Crosslinking step (B)] The cross-linking step (B) is a step of cross-linking the modified starch.

[0028] The crosslinking of the modified starch may be carried out by reacting functional groups of the modified starch with each other, or by reacting functional groups of the modified starch with a crosslinking agent. Among these, from the viewpoint of crosslinking efficiency, it is preferable to react the modified starch with a crosslinking agent.

[0029] The crosslinking agent is preferably one or more compounds selected from the group consisting of polyfunctional epoxy compounds, polybasic acids, and polyfunctional amino compounds.

[0030] Examples of the polyfunctional epoxy compound used as the crosslinking agent include ethylene glycol diglycidyl ether, epichlorohydrin, and epibromohydrin.

[0031] Examples of the polybasic acid used as the crosslinking agent include the same acids as those exemplified as the functional group introducing agent.

[0032] Examples of the polyfunctional amino compound used as the crosslinking agent include polyethyleneimine, ethanolamine, ethylenediamine, propylenediamine, trimethylolmelamine, pentaerythritol, urea, triethylenediamine, triethylenetetramine, hexamethylenetetramine, diethylenetriamine, triethyltetramine, tetraethylenepentamine, and pentaethylenehexamine.

[0033] The crosslinking agents may be used alone or in combination of two or more.

[0034] From the viewpoints of reaction efficiency and reducing environmental load, the crosslinking agent is preferably a polybasic acid, and more preferably at least one selected from the group consisting of itaconic acid, malic acid, succinic acid, and sulfosuccinic acid.

[0035] When the modified starch is crosslinked with the crosslinking agent, the crosslinking can be carried out by mixing the modified starch with the crosslinking agent. From the viewpoint of water absorption performance, the amount of the crosslinking agent used in the crosslinking step (B) is preferably 0.001 to 5 molar parts, more preferably 0.005 to 3 molar parts, per 100 molar parts of the total of monosaccharides constituting the modified starch.

[0036] The mixing of the modified starch and the crosslinking agent in the crosslinking step (B) is preferably carried out by heating and kneading the modified starch, the crosslinking agent, and water using a known twin-screw kneader or the like. From the viewpoint of the efficiency of the crosslinking reaction, the amount of water is preferably 10 to 60 parts by weight per 100 parts by weight of the modified starch. The temperature and time during heating and kneading can be adjusted depending on the scale, etc., but a temperature of 50 to 100°C and a time of 5 to 30 minutes are preferred.

[0037] [Other steps] The production method of this embodiment preferably includes a removal step (C) of removing at least a portion of the salt generated during the process.

[0038] The salt can be removed in the removal step (C) by using a known washing method, and the salt can be removed by mixing the reaction product obtained in the modification step (A) and the crosslinked reaction product obtained in the crosslinking step (B) with an alcohol solvent such as methanol, ethanol, or isopropanol to dissolve the salt in the solvent and then filtering.

[0039] The manufacturing method of this embodiment may also include a pulverization step of pulverizing the crosslinking reaction product obtained in the crosslinking step (B), a classification step of sieving the pulverized product, and a powder mixing step of mixing a known powder flow improver (such as colloidal silica).

[0040] In the production method of this embodiment, the crosslinked reaction product obtained in the crosslinking step (B) may further be surface-crosslinked. The surface-crosslinking of the crosslinked reaction product obtained in the crosslinking step (B) can be carried out by a known method. Examples of the surface-crosslinking agent include polyfunctional epoxy compounds (e.g., ethylene glycol diglycidyl ether, epichlorohydrin, and epibromohydrin) and polybasic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, succinic acid, sulfosuccinic acid, malic acid, itaconic acid, citric acid, and anhydrides thereof). These may be used alone or in combination. Furthermore, the crosslinked reaction product may be used as an aqueous solution, or may be mixed with an alcohol solvent such as methanol, ethanol, or isopropanol.

[0041] The starch-based water-absorbent resin composition obtained by the production method of this embodiment may contain proteins, lipids, saturated fatty acids, unsaturated fatty acids, carbohydrates, dietary fiber, sodium, potassium, calcium, magnesium, phosphorus, iron, zinc, copper, manganese, vitamins, and the like. These may be derived from the raw rice and remain in the water-absorbent resin composition, or may be added in at least one of the steps included in the production method of the present invention or after production. The contents of these components are preferably within a range that does not affect the water-absorbent resin. Furthermore, in the production method of the present invention, a step of removing the above-mentioned components from rice and rice flour may be carried out before the modification step (A).

[0042] The biobased carbon content of the starch-based water absorbent resin composition obtained by the manufacturing method of this embodiment is preferably 70% or more, more preferably 75% or more, from the viewpoint of reducing environmental impact. Biobased carbon refers to carbon derived from biological resources such as plants (hereinafter also referred to as biomass), and the biobased carbon content refers to the proportion of carbon derived from biomass to the total carbon mass constituting a substance. Because the rice starch contained in the rice and rice flour used in the manufacturing method of the present invention is derived from biomass, the more structural units derived from starch, the higher the biobased carbon content of the starch-based water absorbent resin. Furthermore, the biobased carbon content can be further increased by using biomass (e.g., citric acid, itaconic acid, maleic acid, succinic acid, malic acid, and their anhydrides, produced by bioprocesses) as a crosslinker. The biobased carbon content of the starch-based water absorbent resin can be determined by the method described in ISO 16620-2 Biobased Content Part 2: Determination of Biobased Carbon Content (measurement of radioactive carbon (C14) concentration using an accelerator mass spectrometer).

[0043] The water retention capacity (g / g) of the starch-based water absorbent resin composition obtained by the production method of this embodiment can be measured by the method described below, and is preferably 15 or more, more preferably 20 or more, and particularly preferably 30 or more, from the viewpoint of absorption capacity. Moreover, the upper limit is preferably 50 or less, more preferably 45 or less, from the viewpoint of maintaining the gel shape. The water retention capacity can be appropriately adjusted by the amount of crosslinking agent used.

[0044] The starch-based water-absorbent resin composition obtained by the production method of this embodiment can be used for aqueous liquid absorbents, aqueous liquid retention agents, aqueous liquid gelling agents, etc. used in absorbent articles (sanitary products such as disposable diapers and sanitary napkins, anti-condensation agents, agricultural materials (fertilizer raw materials, agricultural and horticultural water retention agents, etc.), soil solidification materials, disaster sandbags, waste blood solidification agents, disposable body warmers, ice packs, alkaline battery materials, cosmetics, pet sheets, cat litter, etc.). The starch-based water-absorbent resin composition obtained by the production method of this embodiment uses raw materials derived from biomass, and is therefore expected to have good biodegradability, and therefore can be preferably used as an agricultural material, among other uses. [Example]

[0045] The present invention will be further explained below with reference to examples and comparative examples, but the present invention is not limited to these. Unless otherwise specified, parts refer to parts by weight. Measurements were carried out in a room at 25±2°C and 50±5% RH, and the temperature of 0.9 wt% physiological saline used to measure water retention was adjusted to 25±2°C in advance.

[0046] <Method for calculating the number of ionic functional groups (carboxyl groups) per monosaccharide unit of modified starch> Five grams of the modified starch obtained in the modification step (A) was pressed into a Briquestting Ring (made of vinyl chloride, 35 mm diameter, 5 mm thick) using a Shimadzu Briquest Press MP-35 to form pellets. The sodium atomic concentration was determined using semi-quantitative analysis with a fully automated wavelength-dispersive X-ray fluorescence analyzer (instrument name: Axios, manufacturer: PANalytical) under X-ray excitation conditions of 20 kV voltage, 120 mA current, and vacuum chamber atmosphere, using the quantitative analysis software Uniquant. The obtained sodium atomic concentration value was substituted for Na in the following equation to calculate the number of ionic functional groups per monosaccharide unit constituting the starch (DS). DS = (162 × Na) / (23-80 × Na)

[0047] <Method for measuring the water retention capacity of saline solution> 1.00 g of a water-absorbent resin composition as a measurement sample was placed in a tea bag (20 cm long, 10 cm wide) made of nylon mesh with a mesh size of 63 μm (JIS Z8801-1:2006), and the bag was immersed in 1,000 ml of physiological saline (salt concentration 0.9%) for 1 hour without stirring, then removed and hung for 15 minutes to drain. The tea bag was then placed in a centrifuge and centrifuged at 150 G for 90 seconds to remove excess physiological saline, and the weight (w1) including the tea bag was measured. The weight (w2) of the tea bag without the measurement sample was measured in the same manner as above. The water retention capacity was calculated using the measured values ​​(w1) and (w2) and the following formula: Water retention amount (g / g)=(w1)-(w2)

[0048] Example 1 A 1 L flask equipped with a Three-One Motor (Shinto Scientific Co., Ltd., Model No. 600G) was placed in a 40°C bath to regulate the temperature. 100 parts of rice flour (variety: Japanese Japonica glutinous rice, sold by Senda Mizuho Co., Ltd., moisture content: 10% by mass) and 800 parts of isopropanol were added to the flask. 82.3 parts of 48% aqueous sodium hydroxide solution and 50.3 parts of sodium chloroacetate were then added and stirred at 80 rpm for 3 hours. The entire contents of the flask were then transferred to a 3 L flask containing 500 mL of methanol. The contents of the 3 L flask were then transferred to a Nutsche tube containing filter paper (Toyo Roshi Kaisha, Ltd., Qualitative Filter Paper No. 2, 110 mm) and filtered under reduced pressure to separate the insoluble matter (residue on the filter paper) and the solution. The residue on the filter paper and 500 parts of 80% aqueous methanol solution were added to a 1 L flask, stirred for 10 minutes using a magnetic stirrer, and then filtered under reduced pressure under the same conditions as above. The precipitate remaining on the filter paper was repeatedly washed with 80% aqueous methanol until no precipitate formed when a 1% aqueous silver nitrate solution (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the filtrate obtained by vacuum filtration. The washed precipitate was spread evenly on a stainless steel tray (32 cm long, 20 cm wide, 3 cm high) and placed in a ventilated, forward-flow dryer set at 40°C for 18 hours at a wind speed of 2 m / s to obtain the modified starch, dried product (1). The number of ionic functional groups in dried product (1) was 0.62 per monosaccharide unit constituting the starch. 100 parts of the dried product (1), 42.8 parts of ion-exchanged water, and 1.0 parts of itaconic acid as a crosslinking agent were placed in a twin-screw kneader [Plastomill kneader (manufactured by Toyo Seiki Seisakusho Co., Ltd.)], and the mixture was kneaded for 10 minutes under conditions of a set temperature of 80 ° C. and a screw rotation speed of 20 rpm. The entire mixture was transferred to a stainless steel tray (length 32 cm, width 20 cm, height 3 cm), and dried at 140 ° C. for 1 hour using a vacuum dryer (manufactured by AS ONE Corporation). The mixture was then pulverized using a household juicer mixer and further classified using a 0.150 mm mesh sieve and a 0.85 mm mesh sieve to obtain a starch-based water-absorbing resin composition (D-1) having a mass average particle diameter of 400 μm.

[0049] <Example 2> A twin-screw mixer (Plastomill mixer, manufactured by Toyo Seiki Seisakusho Co., Ltd.) was charged with 15.9 parts of rice flour (variety: Japanese Japonica polished glutinous rice, sold by Senda Mizuho Co., Ltd., moisture content 10% by mass) and 13.1 parts of isopropanol. 13.1 parts of 48% aqueous sodium hydroxide and 8.0 parts of sodium chloroacetate were then added and mixed for 30 minutes at a set temperature of 80°C and a screw rotation speed of 20 rpm. The entire mixture was then transferred to a 300 mL flask containing 100 mL of methanol. The entire contents of the flask were transferred to a Nutsche flask containing filter paper (Toyo Roshi Kaisha, Qualitative Filter Paper No. 2, 110 mm) and filtered under reduced pressure to separate the insoluble matter (residue on the filter paper) and the solution. The precipitate and 100 parts of 80% aqueous methanol were added to a 300 mL flask and stirred for 10 minutes using a magnetic stirrer, followed by vacuum filtration under the same conditions as above. The residue on the filter paper was repeatedly washed with 80% aqueous methanol solution until no precipitate was generated when a 1% aqueous silver nitrate solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the filtrate obtained by vacuum filtration. The washed residue was spread evenly on a stainless steel tray (32 cm long, 20 cm wide, 3 cm high) and left to stand in a ventilated, forward-flow dryer set at 40°C with an air speed of 2 m / s for 18 hours to obtain a modified starch, dried product (2). The number of ionic functional groups in dried product (2) was 0.52 per monosaccharide unit constituting the starch. 100 parts of the dried product (2), 42.8 parts of ion-exchanged water, and 1.0 parts of itaconic acid as a crosslinking agent were placed in a twin-screw kneader [Plastomill kneader (manufactured by Toyo Seiki Seisakusho Co., Ltd.)], and the mixture was kneaded for 10 minutes under conditions of a set temperature of 80 ° C. and a screw rotation speed of 20 rpm. The entire amount of the kneaded mixture was transferred to a stainless steel tray (length 32 cm, width 20 cm, height 3 cm), and dried at 140 ° C. for 1 hour using a vacuum dryer (manufactured by AS ONE Corporation). The mixture was then pulverized using a household juicer mixer and further classified using a 0.150 mm mesh sieve and a 0.85 mm mesh sieve to obtain a starch-based water-absorbing resin composition (D-2) having a mass average particle diameter of 400 μm.

[0050] Example 3 A starch-based water-absorbing resin composition (D-3) was obtained in the same manner as in Example 1, except that the amount of sodium chloroacetate was changed from 50.3 parts to 8.2 parts.

[0051] Example 4 The same procedure as in Example 1 was carried out except that the amount of sodium chloroacetate was changed from 50.3 parts to 150.9 parts, to obtain a starch-based water-absorbing resin composition (D-4).

[0052] <Example 5> A starch-based water-absorbing resin composition (D-5) was obtained in the same manner as in Example 1, except that 1.0 part of itaconic acid as a crosslinking agent was changed to 1.0 part of malic acid.

[0053] Example 6 A starch-based water-absorbing resin composition (D-6) was obtained in the same manner as in Example 1, except that 1.0 part of itaconic acid as a crosslinking agent was changed to 0.8 parts of ethylene glycol diglycidyl ether.

[0054] Example 7 A starch-based water absorbent resin composition (D-7) was obtained in the same manner as in Example 1, except that rice flour (variety: polished Japanese Japonica glutinous rice, sold by Senda Mizuho Co., Ltd., moisture content 10% by mass) in Example 1 was changed to Bastima rice (produced in India, sold by Seinan Co., Ltd., moisture content 10% by mass).

[0055] Example 8 A starch-based water absorbent resin composition (D-8) was obtained in the same manner as in Example 1, except that rice flour (variety: polished Japanese Japonica glutinous rice, sold by Senda Mizuho Co., Ltd., moisture content 10% by mass) was changed to Bastima rice (produced in Thailand, moisture content 8% by mass).

[0056] Example 9 A starch-based water-absorbing resin composition (D-9) was obtained in the same manner as in Example 1, except that 1.0 part of itaconic acid as a crosslinking agent was changed to 0.89 part of glutamic acid.

[0057] Example 10 A starch-based water-absorbing resin composition (D-10) was obtained in the same manner as in Example 1, except that 1.0 part of itaconic acid as a crosslinking agent was changed to 0.65 parts of sulfosuccinic acid.

[0058] Example 11 A starch-based water-absorbing resin composition (D-11) was obtained in the same manner as in Example 1, except that the crosslinking agent itaconic acid was changed from 1.0 part to 6.4 parts.

[0059] Example 12 A starch-based water-absorbing resin composition (D-12) was obtained in the same manner as in Example 1, except that the crosslinking agent itaconic acid was changed from 1.0 part to 0.15 parts.

[0060] <Comparative Example 1> 120 parts of potato starch (manufactured by Wako Pure Chemical Industries, Ltd., moisture content 16.0% by mass) and 30 parts of maleic anhydride were placed in a Henschel mixer, and a 4.3 wt % aqueous sodium hydroxide solution was added little by little while stirring with the Henschel mixer to prepare a mixture. The resulting mixture was extruded while kneading in a twin-screw extruder (Werner & Pfleiderer, ZSK30) at 90°C and a screw rotation speed of 100 rpm, cooled at room temperature, and then cut into pellets using a pelletizer. The number of ionic functional groups measured using the pellets was 0.2 per monosaccharide unit constituting the starch. Furthermore, the extruded product was pulverized using a household juicer mixer, and then classified using a 0.150 mm mesh sieve and a 0.85 mm mesh sieve to obtain a comparative starch-based water-absorbing resin composition (H-1) having a mass average particle diameter of 400 μm.

[0061] <Comparative Example 2> The same procedure as in Example 1 was carried out, except that 107 parts of rice flour (variety: Japonica glutinous rice produced in Japan, sold by Senda Mizuho Co., Ltd., moisture content 10 mass%) was changed to potato starch (manufactured by Wako Pure Chemical Industries, Ltd., moisture content 16.0 mass%), to obtain a comparative starch-based water absorbent resin composition (H-2).

[0062] The evaluation results are shown in Table 1 or 2.

[0063] [Table 1]

[0064] [Table 2]

[0065] The water-absorbent resin composition obtained by the manufacturing method of the present invention using rice has a larger number of introduced ionic functional groups and is superior in water retention capacity compared to the water-absorbent resin composition of the comparative example using potato starch. In addition, since the modification step is performed using rice and rice flour, the water-absorbent resin composition can be obtained at a lower cost compared to the case where rice starch extracted from rice is used. [Industrial Applicability]

[0066] The production method of the present invention can provide a starch-based water-absorbent resin composition with excellent water absorption performance. Therefore, the method is useful for producing starch-based water-absorbent resin compositions used in hygiene products such as disposable diapers (e.g., baby diapers and adult diapers), napkins (e.g., sanitary napkins), paper towels, pads (e.g., incontinent pads and surgical underpads), and pet sheets (pet urine absorbent sheets), as well as disposable body warmers, gelling agents for batteries, urine gelling agents for portable toilets, ice packs, and water-stopping materials. Furthermore, since the method uses a biomass-derived raw material, the method is particularly useful for producing starch-based water-absorbent resin compositions used as freshness-preserving agents for fruits and vegetables, drip absorbents for meat and seafood, water-retaining agents for plants and soil, and applications involving direct contact with food, such as artificial snow, or applications where the composition is directly applied to the natural environment.

Claims

1. A method for producing a starch-based water-absorbent resin composition, comprising: a modification step (A) of obtaining modified starch having an ionic functional group by using rice and a functional group-introducing agent; and a crosslinking step (B) of crosslinking the modified starch.

2. 2. The method according to claim 1, wherein the number of ionic functional groups in the modified starch is 0.1 to 1.5 per monosaccharide unit constituting the starch.

3. 3. The method according to claim 1 or 2, wherein the crosslinking step (B) is a step of crosslinking the modified starch with a crosslinking agent, and the crosslinking agent is one or more compounds selected from the group consisting of a polyfunctional epoxy compound, a polybasic acid, and a polyfunctional amino compound.

Citation Information

Patent Citations

  • Manufacturing method for starch based water absorbent material

    JP2007222704A